Modeling and Analysis of Unsteady Casson Fluid Flow due to an Exponentially Accelerating Plate with Thermal and Solutal Convective Boundary Conditions - Mehari Fentahun Endalew; Subharthi Sarkar (Journal of Applied Mathematics, 2023)
We intend to analyze the consequence of considering thermal radiation on time-dependent flow of the Casson fluid due to an exponentially accelerated inclined surface along with thermal as well as solutal convective boundary conditions. Fundamental equations governing an isotropic incompressible radiative Casson fluid flow are defined through a set of linear partial differential equations, and exact solutions are derived by using the Laplace transform approach. The numerical findings, obtained using MATLAB software, are presented in graphical and tabular representations based on the obtained analytical solutions of the fundamental equations. This investigation shows that the increment in thermal radiation results in the increment in fluid velocity and temperature distribution including thermal and momentum boundary layer thicknesses. Most interestingly, increasing the mass transfer coefficient results in an increment in the species concentration, velocity profiles, and mass transfer rate. However, the fluid velocity diminishes near the plate upon the increase in plate inclination. The scientific community will benefit greatly from this work since the findings can serve as benchmark solutions using numerical approaches to solve fully nonlinear flow governing problems.